Family History of Colorectal Cancer in BRAF p.V600E mutated Colorectal Cancer Cases - Buchanan, Daniel D. (2013)
BACKGROUND: Previous reports suggest that relatives of CRC-affected probands carrying the BRAF p.V600E mutation are at an increased risk of colorectal (CRC) and extracolonic cancers (ECCs). In this study, we estimated the association between a family history (FH) of either CRC or ECC and risk of CRC with a BRAF p.V600E mutation. METHODS: Population-based CRC cases (probands; aged 18–59years at diagnosis), recruited irrespective of family cancer history, were characterised for BRAF p.V600E mutation and mismatch repair (MMR) status. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using multivariable logistic regression. RESULTS: The 690 eligible probands demonstrated a mean age at CRC diagnosis of 46.9±7.8years, with 313 (47.9%) reporting a FH of CRC and 53 (7.7%) that were BRAF-mutated. Probands with BRAF-mutated, MMR-proficient CRCs were less likely to have a FH of CRC than probands that were BRAF-wildtype (OR=0.46, 95%CI=0.24–0.91; p=0.03). For probands with a BRAF-mutated CRC, the mean age at diagnosis was older for those with a CRC-affected first- or second-degree relative (49.3±6.4 years) compared with those without a FH (43.8±10.2 years; p=0.04). The older the age at diagnosis of CRC with the BRAF p.V600E mutation, the more likely these probands demonstrated a FH of CRC (OR=1.09 per year of age; 95%CI=1.00–1.18; p=0.04). CONCLUSIONS: Probands with early-onset, BRAF-mutated and MMR-proficient CRC were less likely to have a FH of CRC than probands that were BRAF-wildtype. IMPACT: These findings provide useful insights for cancer risk assessment in families and suggest that familial or inherited factors are more important in early onset, BRAF-wildtype CRC.